Dielectric relaxation and defect analysis of Ta2O5 thin films - Ezhilvalavan, S; Tsai, MS; Tseng, TY (My University, 2000)
The presence of defects in thin-film dielectrics often leads to dielectric relaxation as a function of frequency, in which the dielectric constant decreases and the loss tangent increases with increasing frequency. Dielectric relaxation results in charge storage capacity reduction under dynamic random access memory operating conditions. In this work, the dielectric relaxation behaviour of de reactive sputtered Ta2O5 thin film was investigated. Using dielectric dispersion measurements as a function of frequency (100 Hz less than or equal to f less than or equal to 10 MHz) and temperature (27 degrees C less than or equal to T less than or equal to 150 degrees C), we determined the dielectric relaxation and defect quantity of the films and propose an equivalent circuit on the basis of complex capacitance, admittance and impedance spectral studies.